2009
DOI: 10.1038/leu.2009.268
|View full text |Cite
|
Sign up to set email alerts
|

Standardized MRD quantification in European ALL trials: Proceedings of the Second International Symposium on MRD assessment in Kiel, Germany, 18–20 September 2008

Abstract: Assessment of minimal residual disease (MRD) has acquired a prominent position in European treatment protocols for patients with acute lymphoblastic leukemia (ALL), on the basis of its high prognostic value for predicting outcome and the possibilities for implementation of MRD diagnostics in treatment stratification. Therefore, there is an increasing need for standardization of methodologies and harmonization of terminology. For this purpose, a panel of representatives of all major European study groups on chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
225
2
20

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(258 citation statements)
references
References 83 publications
(85 reference statements)
3
225
2
20
Order By: Relevance
“…13,14 Several studies have demonstrated that PCR assays and flow cytometry give complementary results in detecting residual leukemic cells and are currently employed for identification of residual disease and surveillance of disease remission. 15,16 The threshold levels for MRD vary according to the methodology used and to the treatment protocol; however, in most studies, MRD positivity is defined by the presence of X0.01% ALL cells in the marrow. 15,17 New markers for MRD detection in ALL have been recently identified that allow the detection of one leukemic cell among 10 À 5 cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Several studies have demonstrated that PCR assays and flow cytometry give complementary results in detecting residual leukemic cells and are currently employed for identification of residual disease and surveillance of disease remission. 15,16 The threshold levels for MRD vary according to the methodology used and to the treatment protocol; however, in most studies, MRD positivity is defined by the presence of X0.01% ALL cells in the marrow. 15,17 New markers for MRD detection in ALL have been recently identified that allow the detection of one leukemic cell among 10 À 5 cells.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 The threshold levels for MRD vary according to the methodology used and to the treatment protocol; however, in most studies, MRD positivity is defined by the presence of X0.01% ALL cells in the marrow. 15,17 New markers for MRD detection in ALL have been recently identified that allow the detection of one leukemic cell among 10 À 5 cells. 18 The impact of MRD evaluation performed before allogeneic, either related or unrelated hematopoietic stem cell transplantation has been reported in patients with ALL and acute myeloid leukemia and found to be associated with outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…[73][74][75][76] The presence of MSCs harboring these leukemic fusion genes would explain, at least in part, the higher sensibility of the molecular techniques such as quantitative reverse transcriptase PCR over flow cytometry methods for the detection of minimal residual disease because by flow cytometry we just analyze hematopoietic cells. 77 The detection of the BCR/ABL oncogene and lymphoma-specific genetic aberrations in endothelial cells from chronic myelogenous leukemia and B-cell lymphoma patients suggests that endothelial cells may be part of the neoplastic clone [78][79][80] and that hemangioblasts rather than HSCs appear to be target cells for the first oncogenic hit, which could occur during the first Hilden et al 55 Infant AML 45 F Mauvieux et al 59 Pediatric AML 34 F Adult AML 64 F Wuchter et al 57 Childhood Cellular origin and etiology of the infant pro-B ALL C Bueno et al steps of ESC differentiation and/or in hemangioblasts persisting in adults. 81 The cellular organization and relationships among precursors that initiate embryonic angiogenesis and hematopoiesis in humans have been characterized.…”
Section: Environmental Exposures and Delayed Infection Early In Life mentioning
confidence: 99%
“…The major cause of treatment failure is relapse, affecting approximately half of the patients who have achieved CR (2). Survival depends on risk factors such as age, white blood cell (WBC) count, time to CR, disease immunophenotype, cytogenetics, and molecular abnormalities (1), and several studies have shown that detection of minimal residual disease (MRD) in childhood and adult ALL is an independent risk parameter of high clinical relevance (3). Early indicators of disease outcome would be particularly useful for the design of new treatments.…”
mentioning
confidence: 99%